Identification of Superior Forage Pearl Millet (Pennisetum glaucum (L.) R.Br.) Inbred Lines - Meena, Jitendra Kumar; Singode, Avinash; Eswari, K. B.; Ronda, Venkateswarlu; Supriya, Patel; Sagar, Sambari Rahul (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during kharif, (July–November, 2022) at ICAR–Indian Institute of Millet Research (IIMR), Rajendranagar, Hyderabad, India. In this experiment, 81 forage pearl millet (Pennisetum glaucum (L.) R.Br.) lines was evaluated for its genetic diversity and variability. For all variables examined, an analysis of variance revealed a considerable variation between lines. Leaf-to-stem ratio, first-cut and second-cut of green fodder yield, as well as dry fodder yield, all had high PCV and GCV values. For Plant height, Leaf length, Number of leaves tiller-1, Number of tillers plant-1, Stem thickness, and Regeneration ability however, moderate PCV and GCV values have been identified. Plant height, Number of leaves tiller-1, Leaf-to-stem ratio, Green fodder yield in first cut, the Green fodder in second cut, and the yield of dry fodder all showed high heritability and high genetic advance. On the basis of Mahalanobis D2 statistics for clustering, genetic diversity was examined. The Tocher method was used to grouping of genotype lines into 11 clusters. The most lines were found in cluster I (52), followed by cluster VI with 14 lines, cluster III with 6 lines, and cluster IX with 2 lines. Cluster VI has the greatest intra-cluster distance (86.59), followed by clusters I (54.11), III (52.99), and IX (52.30). Between cluster III and IX had observed greater inter-cluster distance of 594.54 followed by cluster III and X (471.67), cluster IX and XI (458.76) and cluster I and IX (410.82). Intercrossing of these clusters lines might be useful to develop better forage pearl millet hybrids.